Model Pengendalian Aset Nirwujud dalam Manajemen Sistem Irigasi - Nugroho Tri Waskitho; Sigit Supadmo Arif; Mochammad Maksum; Sahid Susanto (agriTECH, 2012)
The research aimed at developing model of controlling intangible assets in irrigation system management. The research method consisted of two stages. The first stage was building the model of controlling intangible assets in irrigation system management using neuro-fuzzy. The model had three submodels: (i) knowledge management, (ii) intangible assets, and (iii) performance of irrigation system. The second stage was evaluating the model in Sapon irrigation system in Kulon Progo, Yogyakarta. Data collecting was done by questionnaire and interview on nine Water Use Associations. Data analysis was done by Adaptive Neuro Fuzzy Inference System. The model had been evaluated by correlation coefficient, Mean Absolute Percentage Error and Root Mean Square Error. The research result indicated that the model of controlling intangible assets in irrigation system management could predict intangible assets and performance of irrigation system well. The model linked knowledge management, intangible assets and performance of irrigation system.  Knowledge management felt into four main components: (i) learning organization, (ii) principle of organization, (iii) policy and strategy of organization, and (iv) information and communication technology which controlling intangible assets in irrigation system. Intangible assets consisted of moral intelligence, emotional intelligence, creativity attitude, institutional culture, and farmer participation which  controlling effectiveness of irrigation system.ABSTRAKTujuan penelitian adalah mengembangkan model pengendalian aset nirwujud dalam manajemen sistem irigasi. Metode penelitian terdiri dari dua tahap. Tahap pertama adalah pembangunan model pengendalian aset nirwujud dalam manajemen sistem irigasi dengan prinsip neuro-fuzzy. Model mempunyai tiga sub model yaitu manajemen pengetahuan, aset nirwujud dan kinerja sistem irigasi. Tahap kedua adalah pengujian model di Daerah  Irigasi Sapon di kabupaten Kulon Progo, propinsi Daerah Istimewa Yogyakarta. Pengunpulan data dilakukan dengan kuesioner dan wawancara dengan sembilan Perkumpulan Petani Pemakai Air. Analisa data dilakukan dengan   Adaptive Neuro Fuzzy Inference System. Model dievaluasi dengan koefisien korelasi, Mean Absolute Percentage Error dan Root Mean Square Error. Penelitian menghasilkan bahwa model pengendalian aset nirwujud dalam manajemen sistem irigasi yang menggunakan prinsip neuro-fuzzy dapat memprediksi aset nirwujud dan efektivitas sistem irigasi dengan baik. Model menghubungan manajemen pengetahuan, aset nirwujud dan kinerja sistem irigasi.  Manajemen pengetahuan yang terdiri dari organisasi pembelajar, prinsip organisasi, kebijakan dan strategi organisasi, teknologi informasi dan komunikasi mempengaruhi aset nirwujud sistem irigasi. Aset nirwujud yang terdiri dari kecerdasan moral, kecerdasan emosional, sikap kreatif, budaya lembaga, dan partisipasi petani mempengaruhi efektivitas sistem irigasi.